2015
DOI: 10.1177/0363546515601990
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Exercise- and Sports-Related Injuries in a Population of Young, Physically Active Adults

Abstract: This study quantified the overall incidence of injuries and the large proportion that are caused by exercise and sports among military personnel, a population of healthy, physically active adults. Prevention strategies should focus on running, weight training, basketball, and football. Recommendations include adherence to evidence-based practices to reduce the occurrence of ESR injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 41 publications
2
43
2
2
Order By: Relevance
“…For context, Hauret et al showed in 2015 that over 55% of soldiers experience one or more injuries a year and that soldiers attribute over half of those injuries to exercise or sports, of which running accounted for 43%. 4 This was supported by results from a 2014 injury prevention needs assessment survey, in which over half of the respondents reported an injury in the past year and over a third of those were attributed to running. 38 The third step of the process asks: What works to prevent the problem?…”
Section: Effective In Reducing Injury Riskmentioning
confidence: 89%
See 1 more Smart Citation
“…For context, Hauret et al showed in 2015 that over 55% of soldiers experience one or more injuries a year and that soldiers attribute over half of those injuries to exercise or sports, of which running accounted for 43%. 4 This was supported by results from a 2014 injury prevention needs assessment survey, in which over half of the respondents reported an injury in the past year and over a third of those were attributed to running. 38 The third step of the process asks: What works to prevent the problem?…”
Section: Effective In Reducing Injury Riskmentioning
confidence: 89%
“…3 These MSK injuries, which are predominantly to the lower extremities and lower back, have been referred to as Army training-related overuse injuries. [2][3][4] Yet the need to maintain a vigorous physical training regimen will always be paramount to the Army. It is a paradox that the very physical training activities required or encouraged by the U.S. Army to improve soldiers' physical performance, are also what can most detract from their physical readiness by causing injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Physical training and sports‐related activities account for up to 90% of all musculoskeletal injuries in the US Military, and 80% of these injuries are considered overuse in nature . Nearly all military service members run for physical training, and this accounts for 45% of all exercise and sports‐related injuries in the military . Annual running injury incidence has been reported between 19% and 79% with the greatest percentage of those injuries located at the knee .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data also demonstrate that running is the most frequent cause of exercise-and sport-related injuries in the military [3]. Likewise, there is a high incidence of overuse injuries in recreational athletes, with around 10 % of novice runners reporting injury within a 6-week supervised training program [4].…”
Section: Introductionmentioning
confidence: 99%